Cathepsin K Knockout Mitigates High-Fat Diet–Induced Cardiac Hypertrophy and Contractile Dysfunction - Hua, Yinan (American Diabetes Association, 2013)
The cysteine protease cathepsin K has been implicated in pathogenesis of cardiovascular disease. We hypothesized that ablation of cathepsin K protects against obesity-associated cardiac dysfunction. Wild-type mice fed a high-fat diet exhibited elevated heart weight, enlarged cardiomyocytes, increased left ventricular wall thickness, and decreased fractional shortening. All these changes were reconciled in cathepsin K knockout mice. Cathepsin K knockout partly reversed the impaired cardiomyocyte contractility and dysregulated calcium handling associated with high-fat diet. Additionally, cathepsin K knockout alleviated whole-body glucose intolerance and improved insulin-stimulated Akt phosphorylation in high-fat diet–fed mice. High-fat feeding increased the expression of cardiac hypertrophic proteins and apoptotic markers, which were inhibited by cathepsin K knockout. Furthermore, high-fat feeding resulted in cathepsin K release from lysosomes into the cytoplasm. In H9c2 myoblasts, silencing of cathepsin K inhibited palmitic acid–induced release of cytochrome c from mitochondria and expression of proapoptotic signaling molecules. Collectively, our data indicate that cathepsin K contributes to the development of obesity-associated cardiac hypertrophy and may represent a potential target for the treatment to obesity-associated cardiac anomalies.